2017
DOI: 10.1016/j.plantsci.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of rootstock-mediated nitrogen (N) uptake and root-to-shoot signalling at contrasting N availabilities in tomato

Abstract: Selecting rootstocks for high nitrogen acquisition ability may allow decreased N fertilizer application without reducing tomato yields, minimizing environmental nitrate pollution. A commercial hybrid tomato variety was grafted on a genotyped population of 130 recombinant inbred lines (RILs) derived from Solanum pimpinellifolium, and compared with self- and non-grafted controls under contrasting nitrate availabilities (13.8 vs 1.0mM) in the nutrient solution. Grafting itself altered xylem sap composition under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…However, the absorption of N, P, and K increased when the grafted plants were exposed to Cd, suggesting that Cd stimulates rootstock growth, especially root development. Many studies have reported that using rootstock can increase the nutrient uptake or tolerant abiotic stress in grafted plants [13,[36][37][38]. The present work illustrates that the rootstock growth can also be triggered by abiotic stress factors, such as heavy metal Cd.…”
Section: Uptake Of N P and K In Grafted And Nongrafted Plantssupporting
confidence: 57%
“…However, the absorption of N, P, and K increased when the grafted plants were exposed to Cd, suggesting that Cd stimulates rootstock growth, especially root development. Many studies have reported that using rootstock can increase the nutrient uptake or tolerant abiotic stress in grafted plants [13,[36][37][38]. The present work illustrates that the rootstock growth can also be triggered by abiotic stress factors, such as heavy metal Cd.…”
Section: Uptake Of N P and K In Grafted And Nongrafted Plantssupporting
confidence: 57%
“…This availability of 14 N maximized tomato photosynthetic capacity and increased fruit yields. However, in the organic fertilization treatments heavier in 15 N, both the roots and shoots expanded photosynthetic energy to uptake N assimilates, decreasing source capacities and lowering fruit yields . Tomato plants also indicated thrips during both growing seasons.…”
Section: Resultsmentioning
confidence: 95%
“…The authors suggested that this difference in gene expression could have contributed to the enhanced nitrate uptake and use in grafted tomato plants. Similarly, working with a population of recombinant inbred lines from S. pimpinellifolium, Asins et al (2017) found that selected rootstock genotypes can enhance NUpE in tomato. Based on an analysis of rootstock quantitative trait loci that mediate the leaf N concentration, these authors also demonstrated a genetic relationship between the rootstock hormone (especially cytokinin trans-Zeatin and salicylic acid) and NUpE.…”
Section: Discussionmentioning
confidence: 99%